FRI0379 Chondrocalcinosis frequently occurs at the wrists and hips in the absence of knee involvement. (23rd January 2014) - Abhishek, A.; Doherty, S.; Maciewicz, R.; Muir, K.; Zhang, W.; Doherty, M.
Abstract : Background: The prevalence of chondrocalcinosis (CC) using radiographs of the three areas commonly affected by CC (knees, hips, wrists) has been examined in small studies which provide conflicting information as to whether CC at wrists, hips, and symphysis pubis, or metacarpo-phalangeal joint (MCPJ) calcification can occur in the absence of knee CC. Objectives: To describe the overall and joint specific prevalence of CC, and to compare the prevalence of CC at the hips, symphysis pubis, wrists, and of MCPJ calcification in the presence, and absence of knee CC. Methods: A case-control study embedded in GOAL – the Genetics of Osteoarthritis and Lifestyle study. All participants in this study (n=3, 170) have radiographs of knees, hands, and pelvis which have been scored for structural radiographic changes of OA and for the presence of CC at the knees, hips, symphysis pubis, wrists and for MCPJ calcification. The overall prevalence of CC and 95% confidence interval (CI) were calculated. The prevalence of CC at each joint area; for unilateral, bilateral, and isolated CC (CC at one target joint); and for CC at hips, wrists, and symphysis pubis in the presence, and absence of knee CC was calculated. Results: The overall prevalence (95% CI) of CC in the knee, hip, or hand radiographs was 13.7 (12.5-14.9)%. The knee was the commonest site of CC (8.0%). Other joints involved in a descending order of frequency were: wrists (6.9%), hips (5.0%), symphysis pubis (3.6%), and MCPJ calcification (1.5%). Isolated CC occurred most frequently at the knees (2.6%), and at the wrists (2.3%). There was no predilection for CC to occur on either right or left side at any joint. CC was more likely to be bilateral at knees, wrists and MCPJs, while it was more likely to be unilateral at the hips. The second and third MCPJs were most likely to have calcification. CC was common at other joints in the absence of knee involvement. 44.4% of wrist CC, 45.9% of hip CC, 45.5% of symphysis pubis CC, and 31.3% of MCPJ calcification occurred in the absence of knee involvement. Only 58.4% of GOAL participants with CC at any site (knees, wrists, hips, symphysis pubis, or MCP calcification) could be identified on radiographs of both knees. This increased to 82.4% if the pelvis, and to 81.5% if wrists/hands were also x-rayed. Conclusions: This study concurs with the previous observation that the knee is the commonest site of CC. However, more than 40% people with CC at other joints do not have knee CC and would be missed if knee radiographs were used to screen for individuals with CC. Additionally, only around 80% of people with CC can be identified if radiographs of knees and pelvis, or knees and wrists/hands are performed. Thus radiographs of all three sites i.e. the knees, pelvis and hands/wrists should be performed for complete identification of patients with CC. This finding has significant implications for clinical practice and for case definition in studies of genetic and other risk factors for CC. Disclosure of Interest: None Declared